Facebook e censura - Rodrigues, Victor Cencini (2018)
The research focused on the issue of censorship on Facebook, verify the existence of this censorship and its nature, how this censorship is made and justified to users, how the American social network treats the content published by its users, censorship cases were searched on the EFF website (Eletronic Frontier Foundiation, an American civil rights organization such as freedom of expression on the internet, the survey touched on important Internet issues such as privacy, mass surveillance by governments and the private sector. censorship found range from activists of black movements censored by the denunciation of racist messages they receive, journalists who have been censored for reasons ranging from the disclosure of documents on political scandals or war crimes, research using the terms in their version of the year of 2015, every user entering a social network on the internet had to agree with the terms and privacy policy, the terms under which conditions a publication may be withdrawn